Analisis Profil Psychological Wellbeing Siswa Berbasis Nilai-Nilai Pappaseng - Manippi, Ibnu Hajar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to measure and analyze the level of psychological well-being (PWB) of MTsN 1 students of Makassar based on dimensions rooted in the sublime values of Bugis culture, particularly Pappaseng. The study used a quantitative approach with a descriptive survey design. The instrument used was a Pappaseng-based PWB scale that includes six dimensions: self-acceptance, positive relationships, autonomy, environmental mastery, life purpose, and personal growth. Data were obtained from 60 students of class VIII through Likert scale questionnaire and descriptively analyzed using frequency distribution, mean value, and standard deviation. Results showed that 78.3% of students were in the moderate category of PWB, and 21.7% were in the high category. There were no students belonging to the low category. The average total score of students’ PWB was 157.87 out of a maximum score of 240, which indicated that students had quite good psychological well-being. This finding reinforces the importance of integrating local cultural values as a foundation in character strengthening and adolescent psychological balance. This study recommends the use of Pappaseng values in culturally based counseling guidance services as a relevant and contextual intervention strategy.